Butylated hydroxytoluene induces hyperactivity and alters dopamine-related gene expression in larval zebrafish (Danio rerio). (February 2020) - Liang, Xuefang; Zhao, Yaqian; Liu, Wang; Li, Zhitong; Souders, Christopher L.; Martyniuk, Christopher J.
Abstract: Butylated hydroxytoluene (BHT) is one of the most frequently used synthetic phenolic antioxidants added to food and consumer products such as plastics as a preservative. Due to its high production volume, BHT has been detected in aquatic environments, raising concerns about sub-lethal toxicity. However, there are limited toxicological data for BHT, especially in fish. In this study, zebrafish embryos were exposed to BHT at concentrations ranging 0.01–100 μM for up to 6 days post fertilization (dpf). Acute toxicity was assessed, and experiments revealed that BHT had a 96 h LC50 value of 57.61 μM. At sub-lethal doses (0.1–60 μM), BHT markedly decreased heart rates of zebrafish embryos at 48 h and 72 h by ∼25–30%. Basal and maximal respiration of zebrafish embryos at 24 hpf were decreased by 59.3% and 41.4% respectively following exposure to 100 μM BHT. Behavior in zebrafish was measured at 6 dpf following exposures to 0.01–10 μM BHT. Locomotor behaviors (e.g. total distance moved and velocity) were significantly increased in larvae at doses higher than 0.1 μM BHT. In addition, dark-avoidance behavior was decreased following exposure to 0.01 μM BHT, while conversely, it was increased in zebrafish exposed to 0.1 μM BHT. To investigate potential underlying mechanisms that could explain behavioral changes, transcripts involved in dopamine signaling were measured. Relative expression of dat mRNA was increased in larval fish from the 0.01 μM BHT treatment, while there were no effects on dat mRNA levels at higher concentrations. The mRNA levels of drd3 were decreased in zebrafish from the 1 μM BHT treatment. Taken together, BHT can affect the expression of the dopamine system, which is hypothesized to be related to the abnormal anxiety-associated behavior of larval zebrafish. Graphical abstract: Image 1 Highlights: Butylated hydroxytoluene is an environmental pollutant. Heart rates of zebrafish embryos at 48 h and 72 h were decreased by ∼25–30%. BHT increased locomotor behaviors of zebrafish larvae. Low dose BHT decreased larval dark-avoidance behavior. Levels of dat was increased while drd3 was decreased in response to BHT.